Classification of Urban Images vs. Green Spaces Images Using SVD and KNN - Satria, Ryan (Universitas Bunda Mulia, 2026)
This study aims to classify urban and green land images by employing the Singular Value Decomposition (SVD) method for dimensionality reduction and the K-Nearest Neighbors (KNN) algorithm for classification. The dataset used consists of 600 images (300 urban and 300 green land) with a resolution of 256x256 pixels, sourced from the Kaggle